Effects of the Chromium Content in (TiVNb)100−xCrx Body-Centered Cubic High Entropy Alloys Designed for Hydrogen Storage Applications - Renato Belli Strozi; Daniel Rodrigo Leiva; Guilherme Zepon; Walter José Botta; Jacques Huot (Energies, 2021)
In this paper, we report an investigation of adding a non-hydride forming element in the multicomponent Ti-V-Nb-M system. By the Calculation of Phase Diagrams approach (CALPHAD), the thermodynamic phase stability of the TiVNbT (T = Cr, Mn, Fe, Co, and Ni) was investigated, and Cr was selected as the fourth alloying element due its high tendency to stabilize body-centered cubic solid solutions (BCC). The (TiVNb)100−xCrx alloys (with x = 15, 25, and 35 at.% Cr) were synthesized by arc-melting. The structural characterization reveals that the three alloys were composed of a major BCC phase, which agrees with the thermodynamic calculations. The three alloys absorb hydrogen at room temperature without any activation treatment, achieving a hydrogen uptake of about H/M = 2. The Pressure-Composition-Isotherms curves (PCI) has shown that increasing the Cr amount increases the equilibrium pressures, indicating that tunable H storage properties can be achieved by controlling the alloys’ Cr content.